The penultimate peril - Snicket, Lemony; Helquist, Brett (New York : HarperCollins, 2005)
In this next-to-last chronicle of the lives of the Baudelaire orphans, the siblings pose as concierges at the Hotel Denouement to learn the identities and intentions of certain enemies, encountering characters from their past adventures and pondering the nature of nobility and villainy.
Booklist.
Horn Book.
7.2
5-8
Keywords: Baudelaire, Klaus (Fictitious character) -- Fiction; Baudelaire, Sunny (Fictitious character) -- Fiction; Baudelaire, Violet (Fictitious character) -- Fiction; Brothers and sisters -- Fiction; Disguise -- Fiction; Good and evil -- Fiction; Hotels, motels, etc. -- Fiction; Humorous stories; Orphans -- Fiction; Baudelaire, Klaus (Fictional character) -- Fiction; Baudelaire, Sunny (Fictional character) -- Fiction; Baudelaire, Violet (Fictional character) -- Fiction; Disguise -- Fiction; Good and evil -- Fiction; Hotels and motels -- Fiction; Humorous fiction; Orphans -- Fiction; Siblings -- Fiction